2018
DOI: 10.1016/j.mineng.2018.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Development of a strategy and interpretation of the NIR spectra for application in automated sorting

Abstract: The potential of Near Infrared (NIR) spectroscopy for application in automated sorting was investigated on a sample of iron oxide copper-gold ore. The ore contains a substantial amount of carbonate material which results in excessive acid consumption in the leaching circuit during copper extraction, thereby increasing the processing cost. To separate this unwanted gangue material (carbonate) from the valuable metal (copper), a strategy for classification of ore according to copper and carbonate content was dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Numerous studies of sorting using optical/infrared imaging were identified within the review [19,22,24,[28][29][30][31][32][33][34][35]. It was found that optical and infrared imaging were suitable for sorting a wide range of ores including coal, copper, gold, lead, marble, mineral sands, rare earth elements, tin and zinc.…”
Section: Optical and Hyperspectral Imagingmentioning
confidence: 99%
“…Numerous studies of sorting using optical/infrared imaging were identified within the review [19,22,24,[28][29][30][31][32][33][34][35]. It was found that optical and infrared imaging were suitable for sorting a wide range of ores including coal, copper, gold, lead, marble, mineral sands, rare earth elements, tin and zinc.…”
Section: Optical and Hyperspectral Imagingmentioning
confidence: 99%
“…In many cases, sensor-based sorting systems can be employed for the inspection and physical cleaning of products by means of removing low-quality and foreign, potentially harmful, entities from a given product stream. The main fields of application of sensor-based sorting are recycling, for instance the preparation of glass [9] by removing materials harmful to the melting process such as stones and ceramic glass [10], mining, mainly to remove unwanted gangue from ore, e.g., copper-gold ore [11], as well as agricultural products and foodstuff. Regarding the latter, examples of applications are diverse, including the removal of fungusinfected wheat kernels [12], low-quality rice grains [13], and sunflower seeds [14], or quality insurance in bulgur The turquoise objects represent particles to be accepted, typically the product, and the red ones those to be removed, for instance foreign particles.…”
Section: Related Workmentioning
confidence: 99%
“…Ghosh 39 introduced an infrared thermography-based method for sorting alumina-rich iron ores, while Kern 40 suggested utilizing short-wavelength infrared and dual-energy X-ray transmission sensors for the Hammerlein Sn–In–Zn deposit. Phiri 41 investigated the potential of near-infrared sensors for separating carbonate-rich gangue from copper-bearing particles in a copper–gold ore sample. Tusa 32 advanced the field by evaluating hyperspectral short-wave infrared sensors, combined with machine learning methods, for pre-sorting complex ores.…”
Section: Introductionmentioning
confidence: 99%